Critical Analysis of Radiology's Role in Early Detection of Chronic Diseases - ALHajri, Mohammed Saeed Saad; Alahmari, Abdullah Mubarak Abdullah; Almutairi, Mohammed Hamoud S; Al Ghareeb, Nasreen Abdullah Ahmed; Alnajrani, Hamad Ahmed; ALyami, Majed Ali Abdullah; Alsayegh, Zahra Hilal Essa; Alshehri, Khalid Abdullah Othman; Al matter, Heba Adulmohsen; alsinan , Esraa sameer saeed (Journal of Ecohumanism, 2024)
The first-stage diagnosis of chronic diseases is essential to enhance the client's quality of life and lessen pressure on the health facilities. Radiology must diagnose such diseases in their early stages, thus arresting the advancement of the diseases with utmost efficiency. The following paper assesses the role of radiology in chronic disease screening and features information about novel imaging techniques, namely CT, MRI, and X-ray. This paper aims to identify the use of this imaging in the early diagnosis of chronic illnesses through a literature review of current research and case studies on cardiovascular illnesses, diabetes complications, and chronic respiratory illnesses. These results imply that radiology ought to be integrated into key strategies for the early detection and prevention of chronic diseases.